2020
DOI: 10.1002/ehf2.13076
|View full text |Cite
|
Sign up to set email alerts
|

Nitrates in combination with hydralazine in cardiorenal syndrome: a randomized controlled proof‐of‐concept study

Abstract: Aims Cardiorenal syndrome (CRS) is a common problem of great morbidity and mortality. Hydralazine-isosorbide dinitrate (H-ISDN) may be used in renal failure and may improve exercise capacity in heart failure (HF). Our proof-of-concept study aimed to evaluate early evidence of efficacy, safety, and feasibility of H-ISDN compared with standard of care in CRS. Methods and results This multi-centre, single-blind, randomized trial in Singapore enrolled CRS patients, defined as chronic HF with concomitant renal fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…ESC: In patients with acute HF and SBP > 110 mmHg, intravenous vasodilators may be considered as initial therapy to improve symptoms and reduce congestion. JCS/JHFS: Use of nitrates to improve prognosis and increase activities of daily living HFpEF [ 146 ] NICHE [ 70 ]: In patients with chronic HF with renal failure (89% had concurrent hypertension), hydralazine–isosorbide dinitrate improved 6-MWD compared with standard of care at 6 months, with lower rates of HF hospitalization and mortality, but higher rates of hypotension No restrictions Hypertension in standard-of-care group: N = 20 (90.9%) Hypertension in H-ISDN group: N = 19 (86.4%) SBP in standard-of-care group ( N = 22): 147.0 ± 18.5 mmHg SBP in H-ISDN group ( N = 22): 139.8 ± 23.6 mmHg Not reported NEAT HF-PEF trial [ 71 ]: Patients with HFpEF treated with isosorbide mononitrate were less active and did not have better QoL or submaximal exercise capacity than those who received placebo LVEF ≥ 50% Hypertension in placebo group: N = 54 (92%) Hypertension in isosorbide mononitrate group: N = 45 (88%) SBP in placebo group ( N = 59): 132 ± 18 mmHg SBP in isosorbide mononitrate group ( N = 51): 129 ± 14 mmHg SBP showed a significant decrease in patients who received isosorbide mononitrate compared with those who received placebo. Isosorbide mononitrate group (mean 125; 95% CI 122–128) Placebo group (mean 129; 95% CI 125–132) Treatment difference (mean −3.7; 95% CI −7.2 to −0.3; P = 0.04) Zamani et al 2017 [ 72 ]: Isosorbide dinitrate, with or without hydralazine, did not exert beneficial effects on reflection magnitude, LV remodeling, or submaximal exercise, and was poorly tolerated.…”
Section: Current Drug Therapies For Acute and Chronic Hfpef With Hype...mentioning
confidence: 99%
See 1 more Smart Citation
“…ESC: In patients with acute HF and SBP > 110 mmHg, intravenous vasodilators may be considered as initial therapy to improve symptoms and reduce congestion. JCS/JHFS: Use of nitrates to improve prognosis and increase activities of daily living HFpEF [ 146 ] NICHE [ 70 ]: In patients with chronic HF with renal failure (89% had concurrent hypertension), hydralazine–isosorbide dinitrate improved 6-MWD compared with standard of care at 6 months, with lower rates of HF hospitalization and mortality, but higher rates of hypotension No restrictions Hypertension in standard-of-care group: N = 20 (90.9%) Hypertension in H-ISDN group: N = 19 (86.4%) SBP in standard-of-care group ( N = 22): 147.0 ± 18.5 mmHg SBP in H-ISDN group ( N = 22): 139.8 ± 23.6 mmHg Not reported NEAT HF-PEF trial [ 71 ]: Patients with HFpEF treated with isosorbide mononitrate were less active and did not have better QoL or submaximal exercise capacity than those who received placebo LVEF ≥ 50% Hypertension in placebo group: N = 54 (92%) Hypertension in isosorbide mononitrate group: N = 45 (88%) SBP in placebo group ( N = 59): 132 ± 18 mmHg SBP in isosorbide mononitrate group ( N = 51): 129 ± 14 mmHg SBP showed a significant decrease in patients who received isosorbide mononitrate compared with those who received placebo. Isosorbide mononitrate group (mean 125; 95% CI 122–128) Placebo group (mean 129; 95% CI 125–132) Treatment difference (mean −3.7; 95% CI −7.2 to −0.3; P = 0.04) Zamani et al 2017 [ 72 ]: Isosorbide dinitrate, with or without hydralazine, did not exert beneficial effects on reflection magnitude, LV remodeling, or submaximal exercise, and was poorly tolerated.…”
Section: Current Drug Therapies For Acute and Chronic Hfpef With Hype...mentioning
confidence: 99%
“…The NICHE trial suggested that the combination of hydralazine and isosorbide dinitrate may improve exercise capacity in HF (6-min walk test); however, this effect diminished after adjusting for baseline covariates. Nevertheless, the rates of HF hospitalization and mortality were lower with the combination of hydralazine and isosorbide dinitrate than with standard of care [ 70 ]. The study did not identify significant differences in cardiac structure and function, although the possibility of being underpowered was acknowledged.…”
Section: Current Drug Therapies For Acute and Chronic Hfpef With Hype...mentioning
confidence: 99%